TiO2–Polymer Nano–Composites by Sol–Gel - A. C. Pierre; G. Campet; S. D. Han; S. Y. Huang; E. Duguet; J. Portier (Active and Passive Electronic Components)
Sol-gel processes make it possible to develop new hybrid electrolyte materials of the type ceramic-polymer, known as Nano-Crystallite-Insertion-Material (NCIM). They can be used in reversible alkali electrochemical cells after insertion with cations such as Li+. In the present study, TiO2-polyethylene oxide hybrid materials were synthesized from TiCl4 and from Ti ethoxide. Their structure is analyzed in relation with the processing parameters. A primary evaluation of the nanoscale composite materials for reversible Li insertion was performed.